2012
DOI: 10.3807/josk.2012.16.1.013
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Speed Reconfigurable Logic Operations Based on Single Semiconductor Optical Amplifier

Abstract: We demonstrate an optical gate architecture using a single SOA to perform AND, OR and NOT logic functions. Simple reconfigurable all-optical logic operations are implemented using RZ modulated signals at 40 Gb/s. Contrast ratio and extinction ratio values have been analysed for the different types of logic gates. Maximum extinction ratio and contrast ratio achieved are 19dB and 17.2 dB respectively. Simple structure and potential for integration makes this architecture an interesting approach in photonic compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
(11 reference statements)
0
15
0
Order By: Relevance
“…The second case study, on the other hand, refers to realistic traffic patterns (as shown in Fig. 5(b)) and is described as follows: Num_P = 2, 3,4,6,8,12; the step size is 1 hour with 24 total steps; and the required minimum number of time steps in one period is 1. Table 5 and Fig.…”
Section: Results Of Opd Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The second case study, on the other hand, refers to realistic traffic patterns (as shown in Fig. 5(b)) and is described as follows: Num_P = 2, 3,4,6,8,12; the step size is 1 hour with 24 total steps; and the required minimum number of time steps in one period is 1. Table 5 and Fig.…”
Section: Results Of Opd Modelmentioning
confidence: 99%
“…With the fast development of optical fibers and other optical components, which have the advantages of huge capacity, low signal attenuation, and high performance stability [2,3], they are now widely used as the transmitting infrastructure in communication networks. It has been proven that optical equipment is much more energy efficient than its electronic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Proposals based on polarizationbased logic implementation have some drawbacks, as the state of polarization may change at the reflecting or refracting points along the transmission or propagation path. SOA-based all-optical signal processing has demonstrated great potential in terms of high speed, low power consumption, and optical integration [16]. Only a few works have reported on an all-optical full adder implementation, but with different schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some other logic gates based on silicon micro-ring resonators [23], two photon absorption in silicon waveguides [24], cross phase modulation [25], and single semiconductor optical amplifiers have been investigated [26].…”
Section: Introductionmentioning
confidence: 99%